The supernatural enhancements : a novel - Cantero, Edgar, 1981- (Doubleday, 2014)
"When twentysomething A., the European relative of the Wells family, inherits a beautiful yet eerie estate set deep in the woods of Point Bless, Virginia, it comes as a surprise to everyone--including A. himself. After all, he never knew he had a 'second cousin, twice removed' in America, much less that his eccentric relative had recently committed suicide by jumping out of the third floor bedroom window--at the same age and in the same way as his father had before him"--Amazon.com.